Effect of Addition of Oleic Acid Volume on Magnetite-Oleic Acid Synthesis: FT-IR Analysis - Sani, Sulwiyatul Kamariyah (Indonesian Journal of Science and Pharmacy, 2024)
Synthesis of magnetite modified with oleic acid has been carried out and then characterization was carried out using the FT-IR instrument. This study aims to characterize the effect of variations in the addition of oleic acid volume on the synthesis of magnetite modified with oleic acid using the FT-IR instrument. Synthesis of magnetite modified with oleic acid was carried out using coprecipitation where 50 mL of 25% NH4OH was added to a mixture of 0.046 mol Fe3+ and 0.023 mol Fe2+ in 150 mL of aquabidest until pH 11 was reached, then 3, 6, 9, 12, and 15 mL of oleic acid were added. Characterization of the synthesized material was carried out using the FTIR instrument. The results showed that the addition of oleic acid volume could affect the characteristics of magnetite.